Penerapan Model Inquiry Lesson dengan Google Classroom untuk Meningkatkan Keterampilan Berargumentasi pada Pembelajaran Biologi SMA - Arista Indah Anggraini; Anwari Adi Nugroho; Tri Wiharti (Universitas Sebelas Maret, 2021)
The purpose of this study was to improve the argumentation skills of class X high school students by applying the Inquiry Lesson model with Google Classroom in biology learning. This research is a classroom action research which consists of 4 stages, namely planning, action, observation, and reflection. The subjects of this study were 36 students of class X SMA Negeri in Sukoharjo. The argumentation skill data is taken with an essay test instrument that refers to aspects of claim, data and reasoning. The argumentation skill data was analyzed descriptively quantitatively with the percentage technique. The results showed that the percentage score of argumentation skills in cycle 1 was 78% (28 out of 36 students) and cycle 2 was 92% (33 out of 36 students). The research data shows an increase in argumentation skills from cycle 1 to cycle 2 by 18% through the application of the inquiry lesson model. Argumentation skills are one of the main goals of science learning because students who study science must know scientific explanations about natural phenomena and use argumentation to solve problems. Argumentation skills are important for students as skills needed in the 21st century.